The relationship between leadership styles (Transformational and transactional leadership) and quality of work life. A case study at Sarawak Economic Development Corporation (SEDC), Kuching Sarawak/ Hariz Irfan Junaidi Azizan - Junaidi Azizan, Hariz Irfan (2016)
The purpose of this correlational research was to study the relationship between leadership style (transformational and transactional) and quality of work life by adopting Burns (1978) and Bass and Avolio (1995). Burns (1978) has categorized leadership style into laissez-faire leadership, autocratic leadership, participative leadership, transformational leadership and transactional leadership itself. While Bass and Avolio (1995) has stated that quality of work life has a universal idea that has an alternate philosophical, political and wellbeing related definition. Purposive sampling was used in this study where questionnaires were distributed to 64 respondents which came from various and chosen departments at SEDC, Sarawak then analyzed using IBM Statistic Packages for Science Social (SPSS) version 2.0.